2016
DOI: 10.2139/ssrn.2898636
|View full text |Cite
|
Sign up to set email alerts
|

EFL Indonesian Students' Attitude toward Writing in English

Abstract: Writing is a sophisticated language skill since it requires the ability not only to tailor ideas, but also to construct acceptable sentences to create a meaningful, logical, and comprehensible work. As a result, English as a Foreign Language (EFL) learners have to maximize their efforts to put their thoughts on the paper. This paper is intended to describe the EFL students attitude toward writing. There were 57 students participating in the study. The data was collected by using questionnaire, interview, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 18 publications
3
20
1
1
Order By: Relevance
“…Other than that, apprehensive in writing activities and negative attitude toward academic writing also become factors that determine EFL students' difficulties in writing (Ismail et al, 2010). This facts claimed it is obvious that writing is a difficult skill to be studied (Bailey, 2003;Fareed et al, 2016;and Setyowati & Sukmawan, 2016). Therefore, these problems need solution in order to improve EFL students' ability in writing especially in essay writing such as comparison and contrast essay.…”
Section: E Discussionmentioning
confidence: 99%
“…Other than that, apprehensive in writing activities and negative attitude toward academic writing also become factors that determine EFL students' difficulties in writing (Ismail et al, 2010). This facts claimed it is obvious that writing is a difficult skill to be studied (Bailey, 2003;Fareed et al, 2016;and Setyowati & Sukmawan, 2016). Therefore, these problems need solution in order to improve EFL students' ability in writing especially in essay writing such as comparison and contrast essay.…”
Section: E Discussionmentioning
confidence: 99%
“…Altınmakas & Bayyurt (2018) in their study found that one of the factors influencing undergraduates' writing is their perception about academic writing and disciplinary text genres. Similarly, Setyowati & Sukmawan (2016) in their study reveals that students who have high attitude towards writing view writing as interesting and challenging. Hence, to reach the ability to write needs to built their love towards writing.…”
Section: Introductionmentioning
confidence: 76%
“…In general, mostly students feel writing is a complicated skill. (Karademir & Gorgoz, 2019;Setyowati & Sukmawan, 2016;Mantra & Widiastuti, 2019;Ximenes, Guterres, & Pereira, 2019), Therefore, it can b concluded that morphological interference become a serious problem in learning writing especially for the foreign language learners such as twenty students of C class of English Department state University of Gorontalo. By seeing this fact, an analysis is needed to know what are the types of morphological interference that made by the students.…”
Section: Introductionmentioning
confidence: 99%